(3GdJShjbs (3ebGQHI fXQjI TGedI eOYeI HCSFdI hJeGQjf ddJOQjHs - (3hRGfj(B, (3eMeOs; (3MejOj, RbGjs; (3QeGS, eMeO Cejfs ((3GdLRGFQs (3OGQ GdHGMK ddfTQ hGdETgGQs, 2022)
(3YGdL gGPG GdcJGH GdJShjb ef NdGd GSJYQGV Cge GdJYGQja, eQGMd JWhQ GdJhLgGJ GdeaGgjejI dg, GdCOhGQ GdQFjSjI dhXjaI GdJShjb, CgejJg , fWGbg hefGaYg , eLGdGJ JWHjbg, GdEWGQ GdJfXjej dEOGQI GdJfXje, CgejI EOGQI GdJShjb, hXGFag, GdeeGQSGJ GdJShjbjI, OQGSI hJLRFI GdShb , NUGFUg, CgOGa OQGSI GdShb, JLRFI GdShb, HGdEVGaI Edi Sdhc GdeSJgdc hfeGPL bQGQ GdTQGA, GdeRjL GdJShjbj eagheg hYfGUQg, JShjb GdNOeGJ eagheg hNUGFUg, heQGMd JWhQg hcPG eTGcd JSQjb GdNOeGJ hGdeRjL GdJShjbj GdNOej, GdJShjb GdGSJQGJjLj hGdGSJQGJjLjGJ GdJShjbjI GdJfGaSjI, fXGe GdeYdheGJ hHMhK GdJShjb, GdJShjb GdEdcJQhfj eagheg heJWdHGJ eeGQSJg , GdYhGed GdeSGYOI Ydi GfJTGQg , GdJLGQI GdEdcJQhfjI, YfGUQ eRjL GdJShjb GdEdcJQhfj, eRGjG hYjhH GSJNOGeg, JMOjGJg hSdhc GdeSJgdc GdEdcJQhfj(B.s
Keywords: (3GdCShGbs; (3GdJShjbs